Words of Our Mouth, Meditations of Our Heart : Pioneering Musicians of Ska, Rocksteady, Reggae, and Dancehall - Bilby, Kenneth M., 1953- (Book collections on Project MUSE., 2016)
While singers, producers, and studio owners associated with Jamaican popular music have become international icons, many of the studio musicians who were essential to the sound have remained anonymous. This book of photographic portraits and interview excerpts celebrates over one hundred of these legendary musicians.